2016
DOI: 10.5863/1551-6776-21.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led Model to Reduce Hospital Readmissions in Medically Complex Children

Abstract: OBJECTIVES:This pilot study investigated the feasibility and effect on health care utilization of medically complex children participating in a pharmacist-led model for care coordination. Quality of life and satisfaction with care were secondarily assessed for each patient. METHODS: Four medically complex children were enrolled and contacted by the pharmacist weekly for 5 consecutive months. Time for each encounter with a patient was collected. Each patient's hospital admissions, days of stay, emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Anecdotally, Case 1's owners also reported that while in the process of researching his condition and customizing his diet, ingestion of a nonketogenic treat seemed to trigger a seizure event. 25 By preparing homemade meals, dog owners can personalize each treatment to form the most practical and effective diet for each dog. 11 Like in humans, canine epilepsy has been increasing in incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotally, Case 1's owners also reported that while in the process of researching his condition and customizing his diet, ingestion of a nonketogenic treat seemed to trigger a seizure event. 25 By preparing homemade meals, dog owners can personalize each treatment to form the most practical and effective diet for each dog. 11 Like in humans, canine epilepsy has been increasing in incidence.…”
Section: Discussionmentioning
confidence: 99%
“…24 This dietary approach also reduced or eliminated emergency room visits-a cost, health risk, and quality of life issue that is a concern common among dog owners, individuals with epilepsy, and human caregivers. 25 By preparing homemade meals, dog owners can personalize each treatment to form the most practical and effective diet for each dog. 26 Caution and medical supervision are advised to monitor physiologic responses such as gastrointestinal or allergic reactions, metabolic changes, or vitamin deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies that report the time-consuming process of quality transition of care. 17 Most pharmacist interventions were identified while preparing and counseling the patient for discharge; fewer interventions were identified during the telephone encounters as more time passed since discharge. Overall, this pilot program not only resulted in benefits to the patients from receiving individualized…”
Section: Discussionmentioning
confidence: 99%
“…8,9 As a result, numerous quality improvement efforts in pediatric institutions have focused on tracking and decreasing medication reconciliation errors (MREs). 10,11 However, the reach of these quality improvement efforts is typically limited by the time and clinical expertise required to evaluate a relatively small sample of reconciled medication lists, 8,12 or reliance on a system of voluntary reporting of adverse medication events. 13 Attempts to reduce MREs across an entire healthcare organization face significant barriers.…”
Section: Introductionmentioning
confidence: 99%